2015
DOI: 10.5089/9781484369968.001
|View full text |Cite
|
Sign up to set email alerts
|

Are African Households Heterogeneous Agents?: Stylized Facts on Patterns of Consumption, Employment, Income and Earnings for Macroeconomic Modelers

Abstract: This paper reviews the evidence on how households in Sub-Saharan Africa segment along consumption, income and earning dimensions relevant for quantitative macroeconomic policy models which incorporate heterogeneity. Key findings include the importance of home-grown food in the income and consumption of house-holds well up the income distribution, the lack of formal financial inclusion for all but the richest households, and the importance of non-wage income. These stylized facts suggest that an externally-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…( 2 ) While limited financial participation is a prominent feature of LIC economies, the assumption of segmented labour markets-implying complete labour immobility at business-cycle frequencies-is at odds with the informal and fluid nature of LIC labour markets (Fox, 2015) and with our reading of the evidence on structural transformation in LICs (Gollin et al, 2013 andIMF, 2012). We therefore allow for full labour mobility for the bulk of our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…( 2 ) While limited financial participation is a prominent feature of LIC economies, the assumption of segmented labour markets-implying complete labour immobility at business-cycle frequencies-is at odds with the informal and fluid nature of LIC labour markets (Fox, 2015) and with our reading of the evidence on structural transformation in LICs (Gollin et al, 2013 andIMF, 2012). We therefore allow for full labour mobility for the bulk of our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Diversifying into non-farm economic activities is another way to minimize the food insecurity risk that households in northern Ghana face. Several studies (see [17]- [21]) have shown that rural farm households that combine their farming activities with non-farm income activities are better able to smooth income and consumption. In other words, having a diversified portfolio of income generating activities (and hence a diversified set of income sources) is a sure way to minimize income variability and to ensure a minimum level of income [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hiring for wage jobs often occurs through informal channels. Employers put out the word that they are hiring and rely on referrals from existing employees to …ll the jobs (Funkhouser, 1997a;Fields, 2011b;Fox 2015, Tansel et al, 2015. We do not attempt to model the role played by friend-family-kinship networks in the labor market.…”
Section: C3 Sectoral Labor Supplymentioning
confidence: 99%
“…The equivalent urban unemployment rate, calculated using the o¢ cial government de…nition, is 12:9 percent. 40 Fox (2015) reports that the range is 11 -15 percent in most of Sub-Saharan Africa.…”
Section: Domestic Debt (B)mentioning
confidence: 99%